Pengaruh lama penyimpanan dan jenis kemasan terhadap viabilitas benih rekalsitran pala (Myristica fragrans Hout) - Yudhi Arie Priyanto; Abdul Qadir; MR Suhartanto; Melati Nazar; Ristina Siti Sundari (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Nutmeg seeds are recalcitrant seeds that cannot be stored for long periods of time. The quality of nutmeg seed rapidly declines so that it can affect the productivity of both the seed and its production. This study aims to determine the effect of the storage period and the type of packaging for the storage of nutmeg seeds. Method: This study used a factorial complete block design with the type of packaging factor in several storage periods. Treatment Types of Packaging (K) consisted of four types, namely plastic standing pouch packaging with a size of 14 x 20 cm with a thickness of 0.10 mm (K1), plastic sack packaging which was converted to a size of 17 x 21 cm with a thickness of 0.10 mm (K2), a burlap sack packaging which was converted to a size of 14.5 x 20 cm thickness 0,20 mm (K3), and a rectangular jar measuring 12 x 19 cm thickness 0,20 mm (K4). The storage period was carried out for 12 days (P1), 18 days (P2) and 24 days (P3). The experiment was carried out in room conditions with an average temperature of 28.910C and RH 61.17%. Result: The results showed that storage of nutmeg seeds for 12 days in plastic standing pouch packaging was able to maintain the viability of nutmeg seeds. Storage like this produces seeds with germination capacity (56.25%), moisture content (48.42%), respiration rate (32.35 mmCO2/kg/hour), growth speed (10.5%/etmal), vigor index (9.73) and seed germination capacity. 55.00. Conclusion: Nutmeg seeds should be sown immediately after download. However, with certain storage techniques, nutmeg seeds can still survive with good quality at 12 days of storage in standing pouch packaging with zeolite.